Phosphatidic acid suppresses autophagy through competitive inhibition by binding GAPC (glyceraldehyde-3-phosphate dehydrogenase) and PGK (phosphoglycerate kinase) proteins. Issue 11 (2nd November 2022) - Guan, Bin; Jiang, Yu-Tong; Lin, De-Li; Lin, Wen-Hui; Xue, Hong-Wei
ABSTRACT: Macroautophagy/autophagy is a finely-regulated process in which cytoplasm encapsulated within transient organelles termed autophagosomes is delivered to lysosomes or vacuoles for degradation. Phospholipids, particularly phosphatidic acid (PA) that functions as a second messenger, play crucial and differential roles in autophagosome formation; however, the underlying mechanism remains largely unknown. Here we demonstrated that PA inhibits autophagy through competitive inhibition of the formation of ATG3 (autophagy-related)-ATG8e and ATG6-VPS34 (vacuolar protein sorting 34) complexes. PA bound to GAPC (glyceraldehyde-3-phosphate dehydrogenase) or PGK (phosphoglycerate kinase) and promoted their interaction with ATG3 or ATG6, which further attenuated the interactions of ATG3-ATG8e or ATG6-VPS34, respectively. Structural and mutational analyses revealed the mechanism of PA binding with GAPCs and PGK3, and that GAPCs or ATG8e competitively interacted with ATG3, and PGK3 or VPS34 competitively interacted with ATG6, at the same binding interface. These results elucidate the molecular mechanism of how PA inhibits autophagy through binding GAPC or PGK3 proteins and expand the understanding of the functional mode of PA, demonstrating the importance of phospholipids in plant autophagy and providing a new perspective for autophagy regulation by phospholipids. Abbreviation: ATG: autophagy-related; BiFC: bimolecular fluorescence complementation; co-IP: co-immunoprecipitation; Con A: concanamycin A; ER: endoplasmic reticulum; EZ: elongation zone; FRET-FLIM: fluorescence resonance energy transfer with fluorescence lifetime imaging microscopy; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GST: glutathione S-transferase; MDC: monodansylcadaverine; MZ: meristem zone; PA: phosphatidic acid; PAS: phagophore assembly site; PC: phosphatidylcholine; PE: phosphatidylethanolamine; PGK3: phosphoglycerate kinase; PtdIns3K: phosphatidylinositol 3-kinase; PLD: phospholipase D; TEM: transmission electron microscopy; TOR: target of rapamycin; VPS34: vacuolar protein sorting 34; WT: wild type; Y2H: yeast two-hybrid.